Analisis Manajemen Mushollah Di SMPN 2 Jenggawah - Rofiq Hidayat; Nurul Hafshotus Shofirah; Arina Manasikana; Larasati Afina Salabilla (Jurnal Manajemen Riset Inovasi, 2024)
Musholla management must be carried out systematically and correctly, because musholla can not only be used as a place of worship but can also be used as a place of faith-based learning. This study aims to find out how the management of prayer rooms at SMPN 2 Jenggawah. The emphasis of this study is how the musholla management carries out management so that the musholla at SMPN 2 Jenggawah can function properly according to the observations made. This study uses qualitative research methods with research data collection instruments using interviews, observation, and documentation. The results obtained from this study are that the musholla management process at SMPN 2 Jenggawah is carried out well, both from the planning of the musholla program that is running and the existing mushollah management structure, At SMPN 2 Jenggawah mushollah is not only used as a place of worship, but as a classroom where learners.